L’Église Catholique face à la problématique de la mise en œuvre de l’accord global et inclusif du Centre Interdiocésain en République Démocratique du Congo (31 décembre 2016). - Emmanuel BAKOYOGO TELE, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Catholic church played a major role in order to outcome of the political crisis due to the non holding of the elections foreseen by the Constitution of the Democratic Republic of Congo (DRC) in 2016, election to which the retiring president, Joseph Kabila, that has had finished his two mandates should not participate. In order to find a consensus around the management of the country in case of the non holding of these elections, under the crook of the Catholic church, a political dialogue has been organized the 12th December 12 2016 having permitted the signature of a global and inclusive agreement to the interdiosis center the 31st December 2016.  What ever the signature of the this agreement, it’s application became problematic. Therefore, the political crisis that was supposed to be adjusted lasted, raising the veil thus on the limits of the actions led by the Catholic church.  This article tempts to bring some lightings on the factors that explain the difficulty of the setting in work of this political agreement and the consequences that ensued some in order to clear some corrective measures.